ANALYSIS FAT CONTENT MANGROVE SNAIL ( Telescope telescope) IN THE WATERS OF THE MANGROVE FOREST OF NEGERI LUHU AND FOREST WATERS WAAI VILLAGE MANGROVE - Lestari, Desi Armawati Dwilestari (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Mangrove snails (Telescopium telescopium ) are a type of gastropod that live in brackish water or mangrove forests dominated by mangrove plants. Mangrove snails have a fairly high nutritional content consisting of fat, protein, essential amino acids, and saturated fatty acids. This study aims to determine the fat content of mangrove snails from two different locations, namely in the mangrove forest waters of Negeri Luhu and the mangrove forest waters of Waai Village. This type of research is descriptive qualitative with the object of research being the fat content of mangrove snails. This research was conducted at the Basic Chemistry Laboratory of Pattimura University, Ambon, which was carried out starting on October 14, 2020. Data collection was obtained from the results of the analysis of the fat content of mangrove snails using the soxhlet method. The results of the study showed that from six samples of mangrove snails obtained from two different locations, it was known that the mangrove snail samples in Negeri Luhu had a higher fat content with an average value of 4.5448% compared to the mangrove snail samples in Waai Village which had an average value of 3.3649 %.